2005
DOI: 10.1176/appi.ajp.162.2.361
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of HIV and Chronic Methamphetamine Use on Brain Metabolite Abnormalities

Abstract: Objective-Proton magnetic resonance spectroscopy ( 1 H-MRS) showed decreased neuronal marker N-acetylaspartate and increased glial marker myo-inositol in subjects with chronic methamphetamine use and in subjects infected with HIV. The authors sought to determine whether HIV and a history of chronic methamphetamine use might have additive or interactive effects on brain metabolite abnormalities.Method-1 H-MRS was performed in 68 HIV-positive subjects (24 with a history of chronic methamphetamine use with a life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
121
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(130 citation statements)
references
References 46 publications
8
121
1
Order By: Relevance
“…Quantifying the cumulative impact of mental and physical illnesses on brain and neurocognition will be an especially important next step, as existing evidence suggests the presence of synergistic effects (Carey et al, 2006;Chang, Ernst, Speck, & Grob, 2005;Pfefferbaum et al, 2007).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Quantifying the cumulative impact of mental and physical illnesses on brain and neurocognition will be an especially important next step, as existing evidence suggests the presence of synergistic effects (Carey et al, 2006;Chang, Ernst, Speck, & Grob, 2005;Pfefferbaum et al, 2007).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…By quantifying N-acetylaspartate (NAA), creatine (Cr), choline (Cho), lactate and myo-inositol (mI), MRS offers insight into the neuronal integrity, cell membrane synthesis and turnover, macrophage infiltration, inflammation status, and levels of microglial activation and astrogliosis within the sampled CNS tissue. Marked differences between metabolite concentrations and their ratios in the CNS of both HIV-infected and simian immunodeficiency virus (SIV)-infected subjects and controls are very well documented [12,[52][53][54][55][56][57][58][59][60][61][62]. By studying these metabolite differences at different stages of the infection, it is possible to chronicle when and how regions of interest are impacted.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…While these findings are generally consistent with the preclinical findings on neuronal damage, they do not provide the necessary detail to help localize the damage to a particular basal ganglia pathway or to identify region-specific vulnerabilities to chronic MA exposure in humans. However, Chang et al (2005) recently reported both striatal and pallidal enlargement in abstinent MA abusers based on structural MRI. Their MA abusers showed larger globus pallidus (9.6%) and putamen (9.9%) volumes compared to age and gender comparable controls.…”
Section: Clinical Studiesmentioning
confidence: 99%